Pengaruh Kualitas Pelayanan dan Akses Lokasi terhadap Kepuasan Wisatawan di Glamping Kareumbi Cicalengka - Ajeng Nurazijah; Wentri Merdiani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The tourism sector in Bandung City has experienced significant growth with an increase in the number of tourists from 2022 to 2023. One of the tourist destinations that also receives tourist visits is Glamping Kareumbi Cicalengka. This condition encourages Glamping Kareumbi to increase its competitiveness, especially through improving the quality of service and ease of location access. This study aims to identify and analyze the effect of service quality and location access on the satisfaction of tourists visiting Glamping Kareumbi Cicalengka. The method used in this study is quantitative with a descriptive and verification approach, supported by primary and secondary data. Data were collected by distributing questionnaires via Google Form using an ordinal scale. The population in this study was 214 tourists, and based on the Slovin formula, a sample of 139 respondents was obtained, selected using a simple random sampling technique. Data testing includes validity and reliability tests, normality tests, multiple linear regression analysis, and hypothesis testing with the help of SPSS version 26 software. The analysis results show that service quality has a positive and significant effect on tourist satisfaction, while location access has a significant negative effect. Although the service at Glamping Kareumbi Cicalengka is considered good, accessibility issues such as inadequate roads and minimal directions reduce tourist comfort. Simultaneously, these two variables have a significant effect on tourist satisfaction, with a contribution of 32,7%. Thus, improving location access needs to be a priority to improve the overall tourist experience.